Assessment of Neutrophil Gelatinase-associated Lipocalin in the Brain-dead Organ Donor to Predict Immediate Graft Function in Kidney Recipients. (January 2015) - Muller, Laurent; Nicolas-Robin, Armelle; Bastide, Sophie; Martinez, Orianne; Louart, Guillaume; Colavolpe, Jean-Christian; Vachiery, Florence; Alonso, Sandrine; Lefrant, Jean-Yves; Riou, Bruno
<x xml:space="preserve">Abstract</x> Background: Delayed graft function is a major determinant of long-term renal allograft survival. Despite considerable efforts to improve donor selection and matching, incidence of delayed graft function remains close to 25%. As neutrophil gelatinase-associated lipocalin (NGAL) has been shown to predict acute renal failure, the authors tested the hypothesis that NGAL measurement in brain-dead donors predicts delayed graft function in kidney recipients. Methods: In a prospective, multicenter, observational study, serum NGAL was measured in donors at the time of transfer to operating room. The primary endpoint was the delayed graft function, defined as the need for renal replacement therapy during the first week posttransplantation. Results: Among 159 included brain-dead donors, 146 were analyzable leading to 243 renal transplantations. Of these, 56 (23%) needed renal replacement therapy. Donors' NGAL values were similar in case of both delayed and normal graft function in recipients. The area under the receiver-operating curve for NGAL to predict the need for renal replacement therapy before day 8 was 0.50 (95% CI, 0.42 to 0.59). The area under curve for NGAL to predict failure to return to a normal graft function at day 8 was 0.51 (95% CI, 0.44 to 0.59). Using multivariate analysis, NGAL was not associated to the need for renal replacement therapy (odds ratio, 0.99; 95% CI, 0.98 to1.00) or failure to return to a normal graft function at day 8 (odds ratio, 1.00; 95% CI, 0.99 to 1.00). Conclusion: NGAL measurement in brain-dead donors at the time of recovery failed to predict delayed or normal graft function in kidney recipients.